Sigismund Toduţă. Component Portrait - Burduloi Marta (Sciendo, 2019)
The figure of the composer Sigismund Toduţă is among those creators whose style, although having a constant evolution towards complexity over several creative periods, remains essentially unitary from a stylistic point of view, rendering it recognizable by constant compositional masterpieces throughout his entire work.131 The existence of a significant number of studies, articles, analyses, integrated in various journalistic contexts (magazines, lexicons, doctoral theses), concerning various aspects of Toduţă creation, has made it possible to outline even from the beginning a general picture of the composer's style, a valuable starting point for deepening the research in the spirit of the chosen theme.